2015
DOI: 10.1159/000381671
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Organization of Addiction Medicine Training Across the Globe

Abstract: Background: Over the past decade, addiction medicine training curricula have been developed to prepare physicians to work with substance use disorder patients. This review paper aimed at (1) summarizing scientific publications that outline the content of addiction medicine curricula and (2) evaluating the evidence for efficacy for training in addiction medicine. Methods: We carried out a literature search on articles about addiction medicine training initiatives across the world, using PubMed, PsychINFO and EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 63 publications
1
70
0
1
Order By: Relevance
“…1115 Despite the traditional neglect of addiction medicine in medical curricula, our findings suggest that providing this type of experiential learning in a hospital may be a novel component in the longitudinal education of healthcare providers that could improve the knowledge base and treatment skills of physicians in training. 4 …”
Section: Discussionmentioning
confidence: 99%
“…1115 Despite the traditional neglect of addiction medicine in medical curricula, our findings suggest that providing this type of experiential learning in a hospital may be a novel component in the longitudinal education of healthcare providers that could improve the knowledge base and treatment skills of physicians in training. 4 …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that reflective teaching methods can effectively improve attitudes towards and perceptions of addicted patients among medical doctors [5]. Similarly, few studies explored the effect of interventions aiming to influence illness perceptions among patients [25].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that training in addiction and SUD topics is very effective in improving knowledge and attitudes in students in professional education, such as medicine, psychology and nursing [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…4 With the prevailing variation of addiction medicine education, worldwide, there is a need of competent physicians in addiction. However, it is unknown which core competencies should be covered in every curriculum.…”
Section: Introductionmentioning
confidence: 99%